2020
DOI: 10.1108/ijebr-05-2020-0339
|View full text |Cite
|
Sign up to set email alerts
|

Financing eco-projects: analysis of factors influencing the success of crowdfunding campaigns

Abstract: PurposeThis research identifies and explains the key factors influencing the success of crowdfunding campaigns for eco-projects with the objective of detecting the types of eco-projects that may be most successful in raising funds.Design/methodology/approachThe authors examined over 100 crowdfunding platforms (donation, reward and equity types) and selected 41 active eco-projects for further analysis. Data were collected from the selected platforms on ongoing and historical campaigns. The final sample was deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
(84 reference statements)
2
8
0
Order By: Relevance
“…However, they found that variations are observed when they are divided into subcategories. Prędkiewicz and Kalinowska-Beszczyńska (2020) confirm that updates (positive), comments (positive) and targeted amount (negative) have the strongest impact on the success rate of crowdfunding for eco-projects. They also found a higher probability of success for projects aimed at saving water resources (Prędkiewicz and Kalinowska-Beszczyńska, 2020).…”
Section: Literature Reviewsupporting
confidence: 58%
See 2 more Smart Citations
“…However, they found that variations are observed when they are divided into subcategories. Prędkiewicz and Kalinowska-Beszczyńska (2020) confirm that updates (positive), comments (positive) and targeted amount (negative) have the strongest impact on the success rate of crowdfunding for eco-projects. They also found a higher probability of success for projects aimed at saving water resources (Prędkiewicz and Kalinowska-Beszczyńska, 2020).…”
Section: Literature Reviewsupporting
confidence: 58%
“…Prędkiewicz and Kalinowska-Beszczyńska (2020) confirm that updates (positive), comments (positive) and targeted amount (negative) have the strongest impact on the success rate of crowdfunding for eco-projects. They also found a higher probability of success for projects aimed at saving water resources (Prędkiewicz and Kalinowska-Beszczyńska, 2020). Chan et al (2021) found a clear association between projects that offer customized rewards or social interaction rewards and funding success.…”
Section: Literature Reviewsupporting
confidence: 58%
See 1 more Smart Citation
“…, 2020). By contrast, others find evidence that self-oriented motivations are more likely to dominate (Zhang and Chen, 2019; Prędkiewicz and Kalinowska-Beszczyńska, 2020).…”
Section: Hypothesis Developmentmentioning
confidence: 96%
“…This is a solid alternative to these strategies because institutional resources are often delayed by bureaucratic procedures, while spontaneous fundraising by a private organization depends on the individual willingness of organizational associates. This strategy, which is more efficient, has been used in different areas, such as social entrepreneurship (Morell et al, 2020;Figueroa-Armijos and Berns, 2021;Motero et al, 2021), research (Dalrup et al, 2020), and start-up development (Lee and Lehdonvirta, 2020;Shi et al, 2021), to help different small investors support international entrepreneurial activity (Tiberius and Hauptmeijer, 2021) or cope with international crises, due to ecologic emergencies (Predkiewcz and Kalinowska-Beszczynska, 2020) or pandemics (Saleh et al, 2021). Previously, these areas could be treated in a sufficiently short time because, while public institutions are dedicated to managing problems that are potentially harmful to the community, they are sometimes limited by bureaucracy, political dynamics, priorities on interventions, and temporary or permanent lack of resources; meanwhile, private organizations have difficulty managing some national crises that make it necessary to switch from a profit-making to a social mindset.…”
Section: Introductionmentioning
confidence: 99%